Thermodynamic cycle performances analysis of high temperature refrigerants in a multi-stage heat pump system - Ma Liangdong; Zhang Jili; Zhang Shuyan (2010 International Conference on Mechanic Automation and Control Engineering, 2010)
Based on the select criteria of the refrigerants for high temperature heat pump system, six selected refrigerants, R245fa, R245ca, R236ea, R123, R600 and R134a are used as working fluid of the high temperature heat pump. Three kinds of multi-stage refrigeration circulations, i.e. two-stage compression cycle with one subcooler, two-stage compression cycle with one heat regenerator and one flash tank and three-stage compression cycle with a heat regenerator and two flash tanks, are designed to investigate the multi-stage thermodynamic cycle performances of these refrigerants. The results show that the COP of different thermodynamic cycle increases with increasing number of compression cycle stage. The comprehensive performances of R245fa and R245ca are better than that of other refrigerants in multi-stage compression cycle, which have a good application prospects. And the comprehensive performances of R236ea and R134a are poor compared with other refrigerants.